Electrode molding material, electrode, manufacturing method thereof, recycling method, and electrochemical device
The use of a viscous electrolyte composition in electrode manufacturing addresses mixing and stability challenges, enabling high active material content and stable, odor-free electrode production for electrochemical devices.
Patent Information
- Application Number
- JP2021512132
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-29
- Filing Date
- 2020-03-30
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-03-30
AI Technical Summary
Existing methods for manufacturing electrodes face challenges in mixing raw materials, achieving stable active material content ratios, and dealing with volatile solvents that cause odor and stability issues during electrode production.
A viscous electrolyte composition comprising an ionic substance, a polymer, and a low-molecular-weight organic compound is used to create an electrode molding material that is easy to prepare, allows for improved active material content, and minimizes odor and stability problems, with optional additives like conductive fillers and fiber components for enhanced conductivity and strength.
The solution enables the production of electrodes with high active material content, improved conductivity, and stability, facilitating the manufacturing of high-capacity electrochemical devices while reducing odor and volatility-related issues.
Smart Images

Figure 0007600983000001 
Figure 0007600983000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode molding material, an electrode, a method for producing an electrode, a method for recycling an electrode, and an electrochemical device. [Background technology]
[0002] Electrodes containing an active material have been used in electrochemical devices such as primary batteries, such as lithium primary batteries; nonaqueous secondary batteries, such as lithium ion secondary batteries, lithium metal secondary batteries, sodium ion secondary batteries, potassium ion secondary batteries, magnesium secondary batteries, and aluminum secondary batteries; solar cells, such as dye-sensitized solar cells; capacitors, such as electric double layer capacitors and lithium ion capacitors; electrochromic display devices; electrochemical light-emitting elements; electric double layer transistors; and electrochemical actuators.
[0003] For example, in Patent Document 1, a screw extruder is used to manufacture a positive electrode for an alkali metal polymer battery in which an ion-conductive polymer electrolyte material such as polyethylene oxide, a cathode active material such as vanadium oxide, a conductive filler such as carbon and graphite particles, a lithium salt, and a plasticizer are mixed and extruded onto a metal foil to form a positive electrode film on the metal foil.
[0004] Also, for example, in Patent Document 2, a viscous solution containing polyethylene oxide, carbon, LiV3O8, ethylene carbonate, propylene carbonate, PVdF-HFP copolymer (a copolymer of polyvinylidene fluoride and hexafluoropropylene), and acrylonitrile is applied to an aluminum foil, and then the acrylonitrile is evaporated to produce a positive electrode for a lithium battery in which an electrode film is provided on the aluminum foil. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Special Publication No. 2005-519442 [Patent Document 2] Special Publication No. 2006-522441 Summary of the Invention [Problem to be solved by the invention]
[0006] However, the technique described in Patent Document 1 has a problem in that it is difficult to mix the raw materials of the positive electrode film, making it difficult to increase the content of the active material.
[0007] In addition, the technology described in Patent Document 2 has the problem that a large amount of a volatile solvent such as acrylonitrile is volatilized when forming an electrode film, which can cause problems such as odor. In addition, it is difficult to completely match the volatilization process of the volatile solvent when multiple electrodes are manufactured, making it difficult to stably manufacture electrodes with stable performance.
[0008] Therefore, an object of the present invention is to provide an electrode forming material which is easy to prepare, allows easy improvement of the content of active material, and is unlikely to cause odor or stability problems. Another object of the present invention is to provide an electrode and an electrochemical device using the electrode molding material. [Means for solving the problem]
[0009] As a result of intensive research to achieve the above object, the present inventors have found that an electrode forming material containing a predetermined viscous electrolyte composition is easy to prepare, the content ratio of active material can be easily increased, and problems such as odor and stability are unlikely to occur, and thus the present invention has been completed.
[0010] That is, the present invention aims to advantageously solve the above problems, and the electrode forming material of the present invention is an electrode forming material consisting of at least one active material (A) and a viscous electrolyte composition, the viscous electrolyte composition contains at least one ionic material (S), at least one polymer (P) and an organic composition (PO) containing a low molecular weight organic compound (O) having a molecular weight of less than 10,000, the content of the polymer (P) in the organic composition (PO) is 50 mass% or less, and the low molecular weight organic compound (O) is characterized in that the proportion of compounds having a volatility rate equal to or higher than that of N-methylpyrrolidone is 0 mass% or more and 20 mass% or less. In this way, by using a viscous electrolyte composition containing an organic composition (PO) containing a low molecular weight organic compound (O) and a content rate of the polymer (P) of 50 mass% or less, an electrode forming material that is easy to prepare and easy to increase the content rate of the active material can be obtained. Furthermore, if the proportion of compounds having a volatility rate equal to or higher than that of N-methylpyrrolidone in the low molecular weight organic compound (O) is 20 mass % or less, the occurrence of odors and stability problems during production can be suppressed. In the present invention, the "volatility rate" can be measured at a temperature of 18°C by the method described in the Reference Examples.
[0011] Here, the electrode molding material of the present invention preferably further contains a conductive filler. If the electrode molding material contains a conductive filler, an electrode having excellent conductivity can be formed.
[0012] In the electrode forming material of the present invention, the low molecular weight organic compound (O) preferably contains two or more compounds having a volatility rate lower than that of N-methylpyrrolidone. If the low molecular weight organic compound (O) contains two or more compounds having a volatility rate lower than that of N-methylpyrrolidone, the ionic substance becomes more easily dissolved.
[0013] Furthermore, in the electrode forming material of the present invention, the content of the active material (A) is preferably 50% by volume or more, more preferably 60% by volume or more. When the content of the active material (A) is equal to or more than the above lower limit, a high-capacity electrochemical device can be produced.
[0014] In the electrode molding material of the present invention, the active material (A) is preferably nano-sized. If the active material (A) is nano-sized, an electrode having excellent strength can be formed and the electrochemical reaction can be smoothly promoted.
[0015] Furthermore, the electrode molding material of the present invention preferably further contains a fiber component having a nano-sized fiber diameter. By containing a fiber component having a nano-sized fiber diameter, the strength of the electrode formed using the electrode molding material can be increased.
[0016] In the electrode molding material of the present invention, the organic composition (PO) preferably contains 0% by mass or more and 20% by mass or less of a compound that is liquid at a temperature of 5° C. under atmospheric pressure. By using an organic composition (PO) containing a compound that is liquid at a temperature of 5° C. under atmospheric pressure within the above range, it is possible to obtain an electrode molding material that is difficult to burn.
[0017] In the electrode forming material of the present invention, the viscous electrolyte composition has an ionic conductivity of 1.0×10 at a temperature of 35° C. -4 It is preferable that the viscosity is S / cm or more. The viscous electrolyte composition has an ionic conductivity of 1.0×10 -4 It is preferable that the viscosity is S / cm or more. When the ionic conductivity of the viscous electrolyte composition is equal to or higher than the above lower limit, the electrochemical reaction can be smoothly promoted in the electrochemical device. In the present invention, the "ionic conductivity" refers to the ionic conductivity measured by an AC method, and can be determined by taking the reciprocal of the volume resistivity calculated from the arc diameter of a Nyquist plot obtained by applying an AC voltage in the range of 10 to 100 mV to a sample sandwiched between two parallel stainless steel plates in a thermostatic chamber controlled to a measurement temperature of ±1°C.
[0018] The present invention also aims to advantageously solve the above problems, and the electrode of the present invention is characterized in that it has a portion formed using any one of the above-mentioned electrode molding materials. By using the above-mentioned electrode molding material, it is possible to obtain an electrode having a high content of active material while suppressing the occurrence of problems such as odor and stability.
[0019] Here, the electrode of the present invention preferably has a porosity of 20% by volume or less in the above-mentioned portion. If the porosity of the portion formed using the electrode molding material is 20% by volume or less, the electrochemical reaction can be smoothly promoted. In the present invention, the "porosity" can be determined by calculating the percentage deviation of the actual specific gravity from the theoretical specific gravity at a temperature of 25°C (= {(theoretical specific gravity - actual specific gravity) / theoretical specific gravity} x 100%).
[0020] The electrode of the present invention is preferably formed by forming any one of the above-mentioned electrode forming materials into a sheet-like film. Since the electrode of the present invention maintains its bond only by physical affinity, if the electrode has a sheet-like shape that can easily follow the shape of the adherend such as a current collector, it is easy to maintain close contact with the adherend.
[0021] Furthermore, the electrode of the present invention is preferably formed by attaching the above-mentioned electrode molding material to a current collector.
[0022] Here, in the electrode of the present invention, it is preferable that the collector has a through hole at the portion where the electrode molding material is attached. If the collector has a through hole, the ion conductivity of the electrode can be improved, and the electrode molding material can be well attached at the position where the through hole exists. In addition, if the collector has a through hole, it is possible to easily perform pre-doping.
[0023] In the electrode of the present invention, the current collector preferably has a conductive coating on the surface that comes into contact with the electrode molding material. If the current collector has a conductive coating, the conductivity of the electrode can be increased, and the unevenness of the surface can increase adhesion to the electrode molding material.
[0024] Furthermore, in the electrode of the present invention, the electrode molding material is preferably crosslinked or polymerized. If the electrode molding material is crosslinked or polymerized, an electrode with high strength can be obtained.
[0025] The present invention also aims to advantageously solve the above problems, and the method for producing an electrode of the present invention preferably includes a step of crushing a plurality of strands made of any of the above-mentioned electrode molding materials into a sheet shape. By crushing a plurality of strands made of the electrode molding material, a sheet made of the electrode molding material can be easily obtained with less pressing force, and the sheet can be easily made thinner.
[0026] Furthermore, the method for producing an electrode of the present invention preferably includes a step of shaping any one of the above-mentioned electrode-forming materials and then attaching it to a current collector. By shaping the electrode-forming material and then attaching it to a current collector, the shape of the part made of the electrode-forming material can be easily formed into a desired shape.
[0027] The method for producing an electrode of the present invention preferably includes a step of attaching any one of the above-mentioned electrode forming materials to both sides of a current collector.
[0028] Furthermore, the method for producing an electrode of the present invention preferably includes a step of crushing any of the above-mentioned electrode molding materials with a curved surface having a curvature radius of 100 mm or less. By crushing with a curved surface having a curvature radius of 100 mm or less, the thickness of the part made of the electrode molding material can be easily adjusted.
[0029] In addition, the method for producing an electrode of the present invention preferably includes a step of adjusting the thickness and / or shape by scraping off any of the above-mentioned electrode-forming materials. By scraping off the electrode-forming material, the part made of the electrode-forming material can be easily made to have a desired thickness and / or shape.
[0030] Furthermore, the electrode manufacturing method of the present invention preferably includes a step of roughly adjusting the thickness of any of the above-mentioned electrode molding materials and then fine-adjusting it with a curved surface having a curvature radius of 0.5 mm or more. By roughly adjusting the thickness of the part made of the electrode molding material and then fine-adjusting it with a curved surface having a curvature radius of 0.5 mm or more, it is possible to control the thickness with high precision.
[0031] The electrode manufacturing method of the present invention preferably includes a step of measuring the thickness of the electrode molding material and feedback-controlling the basis weight of the electrode molding material. By measuring the thickness of the electrode molding material and feedback-controlling the basis weight, the basis weight can be easily controlled. In addition, since the above-mentioned electrode molding material contains compounds with a volatility rate equal to or higher than that of N-methylpyrrolidone in a ratio of 0% by mass to 20% by mass, the basis weight can be easily determined from the thickness.
[0032] The present invention also aims to advantageously solve the above problems, and is characterized in that the electrode recycling method of the present invention includes a step of peeling off the electrode molding material from the current collector. In this way, by peeling off the electrode molding material from the electrode formed by providing a portion made of the electrode molding material on the current collector, the electrode can be easily reused.
[0033] Furthermore, the present invention has an object to advantageously solve the above problems, and an electrochemical device of the present invention is characterized by comprising any one of the electrodes described above. If the device comprises the electrodes described above, it can exhibit good electrochemical properties.
[0034] In the electrochemical device of the present invention, the counter electrode of the electrode is preferably made of at least one selected from an alkali metal, an alkaline earth metal, and metallic aluminum. By using a counter electrode made of at least one selected from an alkali metal, an alkaline earth metal, and metallic aluminum, moisture brought in from the electrode can be effectively captured.
[0035] In the electrochemical device of the present invention, at least one of the counter electrode and the separator of the electrode preferably contains an inorganic filler having a moisture trapping ability. If the inorganic filler having a moisture trapping ability is contained, moisture brought in from the electrode can be effectively trapped.
[0036] Furthermore, in the electrochemical device of the present invention, at least one of the counter electrode of the electrode and the separator preferably contains an ionic substance having a moisture trapping ability. If the ionic substance having a moisture trapping ability is contained, moisture brought in from the electrode can be effectively trapped. Effect of the Invention
[0037] According to the present invention, it is possible to provide an electrode forming material which is easy to prepare, has an active material content that is easily increased, and is unlikely to cause odor or stability problems. Furthermore, according to the present invention, it is possible to provide an electrode and an electrochemical device using the electrode molding material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0038] The electrode molding material of the present invention is not particularly limited, and can be used, for example, in forming electrodes of electrochemical devices such as primary batteries such as lithium primary batteries; non-aqueous secondary batteries such as lithium ion secondary batteries, lithium metal secondary batteries, sodium ion secondary batteries, potassium ion secondary batteries, magnesium secondary batteries, and aluminum secondary batteries; solar cells such as dye-sensitized solar cells; capacitors such as electric double layer capacitors and lithium ion capacitors; electrochromic display devices; electrochemical light-emitting devices; electric double layer transistors; and electrochemical actuators. The electrode of the present invention uses the electrode molding material of the present invention, and can be produced by the electrode production method of the present invention without being particularly limited. Furthermore, the electrode of the present invention can be recycled by the electrode recycling method of the present invention. The electrochemical device of the present invention comprises the electrode of the present invention. The electrochemical device described above is preferably a non-aqueous secondary battery, and more preferably a lithium ion secondary battery.
[0039] (molding material for electrodes) The electrode forming material of the present invention comprises at least one active material (A) and a viscous electrolyte composition. The viscous electrolyte composition comprises at least one ionic material (S), at least one polymer (P), and an organic composition (PO) containing a low molecular weight organic compound (O) having a molecular weight of less than 10,000. The electrode forming material may further contain at least one selected from the group consisting of a conductive filler, a solid electrolyte, a fiber component, and an additive.
[0040] <Active material (A)> The active material (A) is not particularly limited, and any active material can be used depending on the type of electrochemical device. The active material (A) contained in the electrode forming material may be composed of only one type of active material, or may be a mixture of two or more types of active materials.
[0041] Among them, as the active material (A), it is preferable to use a nano-sized active material (maximum diameter less than 1 μm), and it is more preferable to use an active material having a volume average particle diameter of 100 nm to 900 nm. If a nano-sized active material is used, the contact interface area with the viscous electrolyte composition becomes large, so that an electrode having excellent strength and an electrode capable of smoothly proceeding with an electrochemical reaction can be formed. In the present invention, the volume average particle size of the active material can be measured in accordance with JIS K8825.
[0042] The content of the active material (A) in the electrode molding material is preferably 50% by volume or more, more preferably 60% by volume or more. When the content of the active material (A) is equal to or more than the lower limit, an electrode capable of producing a high-capacity electrochemical device can be formed.
[0043] <Viscous electrolyte composition> The viscous electrolyte composition is a composition having viscosity, and includes at least one type of ionic substance (S), and an organic composition (PO) containing at least one type of polymer (P) and a low molecular weight organic compound (O) having a molecular weight of less than 10,000. The viscous electrolyte composition requires that the content of the polymer (P) in the organic composition (PO) is 50 mass% or less, and that the proportion of compounds in the low molecular weight organic compound (O) having a volatility rate equal to or higher than that of N-methylpyrrolidone is 0 mass% or more and 20 mass% or less. In this way, by including the low molecular weight organic compound (O) and setting the content of the polymer (P) in the organic composition (PO) to 50 mass % or less, the active material (A) and the viscous electrolyte composition can be easily mixed. Therefore, an electrode molding material that is easy to prepare and has an increased content of the active material can be obtained. In addition, by setting the content of the compound in the low molecular weight organic compound (O) whose volatility is equal to or higher than that of N-methylpyrrolidone to 20 mass % or less, the preparation can be made easier while preventing odor and stability problems from occurring during production.
[0044] [Ionic substances (S)] As the ionic substance, any ionic substance can be used depending on the type of ions used in the electrochemical reaction in the electrochemical device. The ionic substance (S) is preferably a substance that is compatible with the organic composition (PO), which allows the ionic conductivity to be satisfactorily exhibited.
[0045] The ionic substance (S) is preferably a substance that is resistant to moisture. The ionic substance is not particularly limited, and examples thereof include bis(fluorosulfonyl)imide anion, bis(trifluoromethanesulfonyl)imide anion, bis(oxalate)borate anion, difluorooxalateborate anion, ClO4 - , NO3 - , BF4 - , I - , I3 -Salts having the anion such as the above are preferred, and salts having the anion such as a bis(oxalate)borate anion or a difluorooxalateborate anion are more preferred. Specifically, when the electrochemical device is a lithium ion secondary battery or a lithium ion capacitor, the ionic substance may be a lithium salt of the above-mentioned anion, or when the electrochemical device is a magnesium secondary battery, the ionic substance may be a magnesium salt of the above-mentioned anion. Among these, from the viewpoint of increasing the strength of the electrode, it is preferable that the electrode contains a polyvalent cation. If the electrode contains a polyvalent cation, pseudo-crosslinking can be formed between the electrode and the polymer (P). These ionic substances may be used alone or in combination of two or more.
[0046] The concentration of the ionic substance (S) in the viscous electrolyte composition can be, for example, 0.01 mol / L or more and less than 2.5 mol / L. Here, as the ionic substance (S), LiPF6 reacts with moisture in the atmosphere to generate hydrofluoric acid, which may corrode the manufacturing equipment or impair the performance of the electrochemical device, so the content is preferably small, and the content of LiPF6 in the electrode molding material is preferably 5 mass% or less, and more preferably 3 mass% or less.
[0047] [Organic composition (PO)] The organic composition (PO) contains at least one type of polymer (P) in a proportion of 50 mass % or less, and further contains a low molecular weight organic compound (O) having a molecular weight of less than 10,000.
[0048] [Polymer (P)] The polymer (P) is not particularly limited, and may be, for example, a polyether polymer, an acrylic polymer, a polyacrylonitrile polymer, a polyacrylamide polymer, a polyoxazoline polymer, or an aliphatic polycarbonate polymer. Specifically, the polymer (P) may be polyethylene oxide, an ethylene oxide copolymer, a side-chain ethylene oxide polymer, a hydrin rubber, a polytrimethylene ether, a polytetramethylene ether, a polyvinyl acetate, a vinyl chloride-vinyl acetate copolymer, a polyoxazoline, a poly(2-ethyl-2-oxazoline), a side-chain oxazoline copolymer, a polyacrylonitrile, a nitrile rubber, an acrylic acid ester copolymer, a polymethyl methacrylate, a styrene-acrylate copolymer, an acrylic rubber, a poly-N-vinylacetamide, or a polyethylene carbonate. These polymers may be used alone or in combination of two or more. The polymer (P) preferably has a weight average molecular weight of 10,000 or more, and more preferably 100,000 to 30,000,000, as measured in accordance with JIS K7252. The polymer (P) does not include polymers that are polymerized in an electrochemical device.
[0049] Among them, the polymer (P) is preferably a polymer that dissolves in a mixture of an ionic substance (S) and a low molecular weight organic compound (O). Specifically, the polymer (P) is preferably a polymer that increases the viscosity of a liquid mixture when added to the liquid mixture containing the ionic substance (S) and the low molecular weight organic compound (O) in the same ratio as the viscous electrolyte composition. When the mixture of the ionic substance (S) and the low molecular weight organic compound (O) is solid at room temperature, the liquid mixture can be prepared by heating the mixture.
[0050] In addition, from the viewpoint of dissolving the polymer (P) well in the viscous electrolyte composition, it is preferable that the polymer component has a small gel content. The gel content is preferably 20 mass% or less of the polymer (P), more preferably 10 mass% or less, and even more preferably 5 mass% or less. The gel content of the polymer (P) can be determined by adding the polymer to propylene carbonate at a ratio of 5 mass%, stirring and dissolving at 100°C for 12 hours, filtering the insoluble matter with a membrane filter at 100°C, vacuum drying to remove the propylene carbonate, and measuring the weight of the residue.
[0051] The content of the polymer (P) in the organic composition (PO) must be 50% by mass or less, preferably 1% by mass or more, more preferably 3% by mass or more, and preferably 30% by mass or less. If the content of the polymer (P) is 50% by mass or less, even if the content of the active material (A) in the obtained electrode forming material is increased to, for example, 70% by mass or more, the active material (A) and the viscous electrolyte composition can be well mixed. In addition, if the content of the polymer (P) is set to the above upper limit or less, the ionic conductivity of the viscous electrolyte composition can be suppressed from decreasing. Furthermore, if the content of the polymer (P) is set to the above lower limit or more, the formation of an electrode using the electrode forming material can be facilitated.
[0052] [Low molecular weight organic compounds (O) with molecular weights of less than 10,000] The low molecular weight organic compound (O) having a molecular weight of less than 10,000 contains 80 mass% or more of compounds having a volatility lower than that of N-methylpyrrolidone (hereinafter, may be referred to as "low volatility compounds"), and optionally contains 0 mass% or more and 20 mass% or less of compounds having a volatility equal to or higher than that of N-methylpyrrolidone (hereinafter, may be referred to as "high volatility compounds"). When the proportion of the highly volatile compound in the low molecular weight organic compound (O) is 20 mass % or less, the components that volatilize during the formation of the electrode can be reduced, and the occurrence of odor and stability problems can be suppressed.
[0053] Here, the content of the low molecular weight organic compound (O) in the organic composition (PO) is usually 50% by mass or more, preferably 70% by mass or more, preferably 99% by mass or less, and more preferably 97% by mass or less. If the content of the low molecular weight organic compound (O) is set to the above lower limit or more, the preparation of the electrode forming material is facilitated and the decrease in the ionic conductivity of the viscous electrolyte composition can be suppressed. In addition, if the content of the low molecular weight organic compound (O) is set to the above upper limit or less, the formation of an electrode using the electrode forming material can be facilitated.
[0054] -Low volatility compounds- Here, examples of the low volatility compound include, but are not limited to, trisethylhexyl phosphate, adiponitrile, 1,3-propane sultone, glutaric anhydride, succinic anhydride, succinonitrile, tributyl phosphate, tetraglyme, diglycolic anhydride, sulfolane, ethyl methyl sulfone, dimethyl sulfone, trisbutoxyethyl phosphate, sulfolene, diethyl sulfone, ethylene sulfate (1,3,2-dioxathiolane-2,2-dioxide), vinyl ethylene carbonate, ethylene carbonate, N-methyloxazolidone, propylene carbonate, fluoroethylene carbonate, triglyme, triethyl phosphate, citraconic anhydride, methyl carbamate, and dimethylimidazolidinone. Among these, from the viewpoint of further reducing the components that volatilize during the formation of the electrode, trisethylhexyl phosphate, adiponitrile, 1,3-propane sultone, glutaric anhydride, succinic anhydride, succinonitrile, tributyl phosphate, tetraglyme, diglycolic anhydride, sulfolane, ethyl methyl sulfone, dimethyl sulfone, trisbutoxyethyl phosphate, sulfolene, diethyl sulfone, ethylene sulfate (1,3,2-dioxathiolane-2,2-dioxide), vinyl ethylene carbonate, ethylene carbonate, N-methyl oxazolidone, propylene carbonate, fluoroethylene carbonate, triglyme, etc. Preferred are organic compounds having a higher volatility than triethyl phosphate, and more preferred are organic compounds having a higher volatility than propylene carbonate, such as trisethylhexyl phosphate, adiponitrile, 1,3-propane sultone, glutaric anhydride, succinic anhydride, succinonitrile, tributyl phosphate, tetraglyme, diglycolic anhydride, sulfolane, ethyl methyl sulfone, dimethyl sulfone, trisbutoxyethyl phosphate, sulfolene, diethyl sulfone, ethylene sulfate (1,3,2-dioxathiolane-2,2-dioxide), vinyl ethylene carbonate, ethylene carbonate, and N-methyloxazolidone. The above-mentioned organic compounds may be used alone or in combination of two or more. Among them, from the viewpoint of improving the solubility of the ionic substance while reducing the components volatilized during the formation of the electrode, it is preferable to use two or more of the above-mentioned organic compounds in combination as the low volatility compound, and more preferably to use three or more of them in combination. The proportion of the low volatility compound in the low molecular weight organic compound (O) is not particularly limited as long as it is 80 mass % or more, but is preferably 90 mass % or more.
[0055] -Highly volatile compounds- Furthermore, the high volatility compound is not particularly limited, and examples thereof include N-methylpyrrolidone, γ-butyrolactone, dimethyl oxalate, vinylene carbonate, dimethyl sulfoxide, trimethyl phosphate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl acetate, ethyl propionate, and propyl propionate. Among these, from the viewpoint of reducing the amount of volatilization during electrode formation, organic compounds such as N-methylpyrrolidone, γ-butyrolactone, dimethyl oxalate, vinylene carbonate, dimethyl sulfoxide, and trimethyl phosphate, which have a volatility rate equal to or higher than that of trimethyl phosphate, are preferred. The above organic compounds may be used alone or in combination of two or more.
[0056] The proportion of the high volatility compound in the low molecular weight organic compound (O) is not particularly limited as long as it is from 0 mass % to 20 mass %, but is preferably 10 mass % or less.
[0057] The low molecular weight organic compound (O) preferably has a content of 0% by mass or more and 20% by mass or less, more preferably 10% by mass or less, of a compound that is liquid at atmospheric pressure at a temperature of 5° C. If the content of the compound that is liquid at atmospheric pressure at a temperature of 5° C. is equal to or less than the upper limit, it is possible to obtain an electrode molding material that is difficult to burn, and to prevent the volatilized compound from adhering to the surroundings as a liquid and causing mechanical failure, etc.
[0058] Here, examples of compounds that are liquid at a temperature of 5°C under atmospheric pressure include, but are not limited to, trisethylhexyl phosphate, adiponitrile, 1,3-propane sultone, tributyl phosphate, tetraglyme, trisbutoxyethyl phosphate, vinyl ethylene carbonate, propylene carbonate, triglyme, triethyl phosphate, citraconic anhydride, N-methylpyrrolidone, γ-butyrolactone, trimethyl phosphate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl acetate, ethyl propionate, and propyl propionate.
[0059] [Properties of viscous electrolyte composition] The viscous electrolyte composition is not particularly limited, but preferably has the following properties.
[0060] 〔viscosity〕 The viscous electrolyte composition preferably has components that are compatible with each other, and is more preferably liquid under atmospheric pressure at a temperature of 35° C. The viscosity of the viscous electrolyte composition at a temperature of 25° C. is preferably 10 mPa s or more, more preferably 20 mPa s, and even more preferably 50 mPa s or more. In the present invention, the term "viscosity" refers to a viscosity measured at a temperature of 25°C using an EMS viscometer (Kyoto Electronics Manufacturing Co., Ltd., EMS-1000S) under sealed conditions with a motor speed of 1000 rpm so that the organic composition does not volatilize and moisture in the air does not get mixed in. The viscosity measured by this measurement method is basically the same as the value measured in accordance with JIS Z8803. The viscosity of the viscous electrolyte composition can be adjusted by changing the composition of the viscous electrolyte composition. Specifically, for example, the viscosity of the viscous electrolyte composition can be increased by blending a high-viscosity compound or increasing the concentration of an ionic substance. Furthermore, when it is desired to know the composition that will become a liquid when solid compounds are mixed, equal amounts of all compounds used in the formulation of the composition are mixed, and the whole is heated to a temperature equal to or higher than the melting point of the compound with the highest melting point among those compounds until it is melted, and then cooled to the temperature at which it is desired to use it as a liquid. If the whole remains liquid, it can be used as is, but if some of it becomes solid, the composition of the supernatant can be quantified by gas chromatography or liquid chromatography to determine the composition that will become a liquid.
[0061] [Ionic Conductivity] Furthermore, the viscous electrolyte composition has an ionic conductivity of 1.0×10 -4 The viscous electrolyte composition preferably has an ionic conductivity of 1.0×10 S / cm or more at a temperature of −20° C. -4 When the ionic conductivity of the viscous electrolyte composition is equal to or higher than the lower limit, the electrochemical reaction can be satisfactorily promoted in an electrochemical device including an electrode formed using the electrode forming material.
[0062] <Conductive filler> The conductive filler, which is an optional component, is not particularly limited, and any conductive filler that can be used in the field of electrochemical devices, particularly a particulate conductive filler, such as acetylene black, ketjen black, graphite, graphene, etc., can be used. By including the conductive filler, an electrode with excellent conductivity can be formed. The content of the conductive filler in the electrode forming material is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and preferably 100 parts by mass or less, more preferably 70 parts by mass or less, per 100 parts by mass of the viscous electrolyte composition. If the content of the conductive filler is equal to or more than the lower limit, the conductivity of the electrode can be sufficiently increased. If the content of the conductive filler is equal to or less than the upper limit, it is possible to prevent the electrode forming material from being difficult to prepare due to the difficulty in mixing.
[0063] <Solid electrolyte> From the viewpoint of expecting an improvement in safety, the electrode forming material may contain an ion-conductive inorganic solid electrolyte (SE). Since the inorganic solid electrolyte (SE) is nonvolatile and in many cases is nonflammable or has low flammability, the higher the ratio of the inorganic solid electrolyte (SE) mixed in the electrode forming material, the higher the safety of the electrochemical device. The inorganic solid electrolyte (SE) may be particulate or fibrous. The preferred mixing ratio of the inorganic solid electrolyte (SE) per total volume of the ionic substance (S), the organic composition (PO), and the inorganic solid electrolyte (SE) is preferably 10% by volume or more, more preferably 30% by volume or more, even more preferably 50% by volume or more, and particularly preferably 70% by volume or more. The particle diameter of the inorganic solid electrolyte (SE) is preferably smaller than that of the active material (A) from the viewpoint of increasing the volume fraction of the active material in the electrode.
[0064] The inorganic solid electrolyte (SE) may be, for example, an ion-conducting ceramic. The inorganic solid electrolyte may be, for example, a Li-PS-based conductor (e.g., Li7P3S 11 ), Li-Ge-PS-based conductors (e.g., Li 10 GeP2S 12 ), Li-Si-PS-Cl-based conductors (e.g., Li 9.54 S 1.74 P 1.44 S 11.7 Cl 0.3 ), Li-La-Zr-O conductors (e.g., Li7La3Zr2O 12 ), Li-Al-Ge-PO conductors (e.g., Li 1.5 Al 0.5 Ge 1.5 P3O 12 ), Li-La-Zr-O conductors (e.g., Li7La3Zr2O 12 ), Li-La-Zr-Ta-O conductors (e.g., Li 6.75 La3Zr 1.75 Ta 0.25 O 12 ), Li-La-Ta-O conductors (e.g., LiLa 0.51 TaO 2.94 ), Li-Al-Si-P-Ti-O conductors (e.g., Li2Al2SiP2TiO 13), Li-Ti-Al-Si-PO conductors (e.g., Li 1.4 Ti 1.6 Al 0.4 P3O 12 ), and Li-Ba-Cl-O based conductors (e.g., Li 2.99 Ba 0.005 O 1+x Cl 1-2x ) and other lithium ion conductors; β-alumina, Na-Ba-Cl-O based conductors (e.g., Na 2.99 Ba 0.005 O 1+x Cl 1-2x ) and other sodium ion conductors; Rb-Cu-I C conductors (e.g., RbCuI 1.75 C l3.25 ) and other copper ion conductors; Ag-IWO-based conductors (for example, Ag6I4WO4) and other silver ion conductors;
[0065] <Fiber components> The optional fiber component is not particularly limited, and it is preferable to use a fiber component with a nano-sized fiber diameter (maximum diameter less than 1 μm), and more preferably to use a fiber component with an average fiber diameter of 0.4 nm to 500 nm. If a fiber component with a nano-sized fiber diameter is blended, it helps the components contained in the electrode molding material to be united, and an electrode with excellent strength can be formed. The fiber diameter can be measured using a microscope such as a scanning electron microscope or a transmission electron microscope. The fiber diameter before blending may be nano-sized, or may be nano-sized after being kneaded as an electrode molding material, but it is important that nano-sized bridges are formed between the particles of the active material (A). When the electrode of the present invention is observed under a microscope, it is preferable that there are 10 or more bridges in a field of view of 100 μm square, and more preferably there are 20 or more bridges. If a volatile organic compound is present and it is not suitable for observation, it is preferable to dry the electrode before observation.
[0066] Here, the fiber component having a nano-sized fiber diameter is not particularly limited, and examples thereof include carbon nanotubes, carbon nanofibers, cellulose nanofibers, PTFE (polytetrafluoroethylene) nanofibers, PVdF (polyvinylidene fluoride) nanofibers, polyacrylonitrile nanofibers, etc. In addition, by using an electrostatic spinning method (electrospinning method), nanofibers of any polymer can be prepared and used. Among them, as fiber components having a nano-sized fiber diameter, carbon nanotubes, PTFE nanofibers, and electrostatically spun polymer nanofibers are preferred in terms of fiber fineness. The amount of the fiber component is not particularly limited, and is, for example, preferably 8 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less, per 100 parts by mass of the active material (A). If the content of the fiber component is equal to or less than the above upper limit, a decrease in the electrode density can be suppressed.
[0067] <Additives> The optional additives are not particularly limited, and any additives that can be used in the field of electrochemical devices, such as electrode protectants and flame retardants, can be used. In addition, it is preferable to use an additive having a low volatility, it is more preferable to use a compound having a volatility lower than that of triethyl phosphate, and it is even more preferable to use a compound having a volatility lower than that of polycarbonate.
[0068] [Electrode protection agent] The electrode protecting agent is not particularly limited, and any electrode protecting agent that can be used in the field of electrochemical devices can be used. Specifically, examples of the negative electrode protecting agent include fluoroethylene carbonate, vinylene carbonate, 1,3,2-dioxathiolane-2,2-dioxide, 1,3-propane sultone, butane sultone, vinyl ethylene carbonate, and diallyl carbonate.
[0069] [Flame retardant] As the flame retardant, phosphates having 24 or less carbon atoms, phosphites having 24 or less carbon atoms, phosphazenes, etc. can be used. Among them, it is preferable to use phosphates as the flame retardant.
[0070] Further, as additives, whiskers, red phosphorus, aluminum hydroxide, magnesium hydroxide, antimony, cyclophosphazene oligomer, silica, alumina, zirconia, barium titanate, melamine, melamine cyanurate, ammonium carbonate, ammonium chloride, sodium bicarbonate, oxybisbenzylhydrazide, and the like can also be used. The content of each additive in the electrode forming material is not particularly limited, but is usually 5 mass % or less.
[0071] <Physical properties of electrode molding material> The electrode forming material is preferably in a clay-like or powder form, and more preferably in a clay-like form. In addition, the electrode molding material preferably has a porosity of 20% by volume or less, or can be compressed to 20% by volume or less. By using an electrode molding material having the above-mentioned porosity, a high-density electrode can be formed.
[0072] <Preparation of electrode molding material> The electrode forming material can be prepared by mixing the above-mentioned components in any order without any particular limitation. In particular, from the viewpoint of ease of preparation, the electrode forming material is preferably prepared by mixing the organic compound in advance, and then adding and mixing the inorganic compound. In addition, when the mixture of the ionic substance (S) and the organic composition (PO) is in a liquid state, it is preferable that the ionic substance (S) and the organic composition (PO) are used in the preparation of the electrode forming material after being made into a liquid mixture. If the prepared electrode forming material is not to be used immediately, it is preferable to store it in a sealed container or with a protective film attached thereto to prevent the components contained therein from volatilizing off.
[0073] (electrode) The electrode of the present invention includes a portion formed using the electrode molding material of the present invention. That is, the electrode of the present invention may be composed only of the electrode molding material, or may have a portion formed using the electrode molding material on the surface of a collector or the like. In this way, by using the electrode molding material of the present invention, an electrode having a high content of active material can be obtained while suppressing the occurrence of odor and stability problems. In the electrode of the present invention, a plurality of portions formed using the electrode molding material may be laminated. The laminated plurality of electrode molding materials may have different compositions. When the portions formed using the electrode molding material are laminated on the current collector, the ratio of the viscous electrolyte composition in the electrode molding material is increased from the portion closer to the current collector to the portion farther from the current collector, so that the output of the electrochemical device is less likely to decrease even if the electrode thickness is increased.
[0074] Specifically, the electrode of the present invention may be, for example, an electrode formed from the electrode forming material of the present invention in any shape, such as a sheet, or may be formed by attaching the electrode forming material to a current collector. Here, the electrode may have a uniform thickness or a gradient in thickness. An electrode with a gradient in thickness can be produced, for example, by nipping with rolls having different clearances at both ends. Since the electrode of the present invention maintains its bond only through physical affinity, if the electrode is in a sheet form that can easily conform to the shape of the adherend, such as a current collector, it is easy to maintain close contact with the adherend.
[0075] Here, when the electrode molding material is attached to the current collector, the shape of the electrode molding material to be attached can be any shape. The electrode molding material may be attached to only one side of the current collector, or may be attached to both sides of the current collector. Furthermore, a frame may be provided on the outside of the electrode molding material for the purpose of regulating the thickness or isolating the electrode molding material from the outside. The frame is preferably insulating and can be formed, for example, from a polymer material. The method of formation may involve arranging a frame part that has already been shaped, or forming the frame on the spot by supplying molten resin with a dispenser, or forming the frame by inkjet printing.
[0076] Furthermore, the current collector preferably has a through hole at the site where the electrode molding material is attached. If the current collector has a through hole at the site where the electrode molding material is attached, the electrode molding material can be filled into the through hole, and the electrode molding material can be attached well. If the current collector has a through hole, for example, when an active material having an initial irreversible capacity is used as the active material (A), pre-doping can be easily performed using the vertical pre-doping method. Furthermore, by having a through hole, the ratio of the active material inside the electrochemical device can be increased, and the energy density can be improved. Examples of current collectors having a through hole include punching metal, expanded metal, mesh, and carbon nonwoven fabric. Even if the current collector does not have a through hole, it is possible to perform doping by directly contacting a doping source such as lithium metal with the part formed using the electrode forming material. Specifically, the doping source may be attached to the current collector or may be brought into contact with the part formed using the electrode forming material.
[0077] In addition, the collector preferably has a conductive coating on the surface that contacts the electrode molding material. If the collector has a conductive coating on the surface that contacts the electrode molding material, the conductivity of the electrode can be increased, and the unevenness of the surface can increase the adhesion to the electrode molding material. The conductive coating is not particularly limited, and any conductive coating that can be used in the field of electrochemical devices can be used.
[0078] The portion formed using the electrode molding material preferably has a porosity of 20 volume % or less, more preferably 15 volume % or less. If the portion formed using the electrode molding material has a porosity of the above upper limit or less, the electrochemical reaction can proceed smoothly in the electrochemical device.
[0079] In addition, in the portion formed using the electrode molding material, the electrode molding material is preferably crosslinked or polymerized, because if the electrode molding material is crosslinked or polymerized, an electrode with high strength can be obtained. The method for crosslinking or polymerizing the electrode forming material is not particularly limited, and known methods such as heating and irradiation with ultraviolet rays or electron beams can be used.
[0080] (Electrode manufacturing method) The method for producing an electrode of the present invention can be used to produce the electrode of the present invention described above.
[0081] In the method for producing an electrode of the present invention, the electrode can be produced by molding the electrode-forming material in an open atmosphere, without any particular limitations. Here, the term "open atmosphere" refers to an atmosphere in which the electrode-forming material is in contact with the electrode-forming material and is not saturated with vapor from the electrode-forming material, such as an atmosphere in which an air current is present or an atmosphere that is evacuated. In order to prevent adhesion of moisture, it is preferable to manufacture the electrodes at a temperature equal to or higher than the dew point of the manufacturing atmosphere. For the same reason, it is preferable not to use a processing machine that uses water as a coolant (or heat medium) in the manufacture of the electrodes.
[0082] Furthermore, in the electrode manufacturing method of the present invention, an electrode forming material is used that has a low proportion of compounds whose volatility is equal to or greater than that of N-methylpyrrolidone. Therefore, unlike the manufacture of electrodes using slurries that contain a large amount of solvent, electrodes can be manufactured without carrying out a drying step for drying the electrode forming material.
[0083] When manufacturing an electrode composed only of an electrode molding material, the electrode can be manufactured by molding the electrode molding material into a desired shape, such as a sheet, without any particular limitation, and then optionally crosslinking or polymerizing the material to manufacture the electrode. In addition, when forming the electrode forming material into a sheet, it is preferable to crush a plurality of strands of the electrode forming material to form the sheet, without any particular limitation, from the viewpoint of easily obtaining a sheet made of the electrode forming material and making the sheet thinner. Here, the cross-sectional shape of the strands may be a circle, an ellipse, a triangle, a square, or other polygon. From the viewpoint of not generating pores in the electrode, shapes that do not have depressions, such as a star shape, are preferable.
[0084] In addition, when manufacturing an electrode by attaching an electrode forming material to the surface of a current collector, the electrode can be manufactured by forming the electrode forming material into a desired shape and then attaching it to one or both sides of the current collector, without any particular limitation. If the electrode forming material is shaped and then attached, the shape of the part made of the electrode forming material provided on the current collector can be easily made into the desired shape. For example, a sheet-shaped electrode forming material can be continuously formed on a metal roll, and then the electrode forming material can be intermittently cut out perpendicular to the flow direction on the metal roll, so that the divided electrode forming material, which is not a continuous body, can be transferred to the current collector. Here, when shaping is performed after attaching to the current collector, or when attaching and shaping are performed simultaneously, it is preferable to limit the force applied and the content of the work so as not to deform or damage the current collector. When the electrode-forming material is applied to both sides of the current collector, it is preferable that the electrode-forming material is applied to both sides of the current collector at approximately the same time, and more preferably at the same time.
[0085] When an electrode is produced as described above, it is preferable to include a step of adjusting the shape and / or thickness of the electrode forming material.
[0086] The shape of the electrode-forming material can be easily adjusted, for example, by scraping off the electrode-forming material. The thickness of the electrode-forming material can be easily adjusted, for example, by crushing the electrode-forming material with a roll or the like, or by scraping off the electrode-forming material.
[0087] Here, when the thickness is adjusted by squeezing the electrode forming material, it is preferable to squeeze the electrode forming material on a curved surface with a radius of curvature of 100 mm or less from the viewpoint of easily adjusting the thickness. In addition, when squeezing, squeezing while controlling the clearance to a constant value makes it easier to obtain an electrode with a uniform thickness. In addition, the curved surface with a radius of curvature of 100 mm or less is preferably in the shape of a roll, and more preferably rotated. The rotation may be at the same speed as the electrode forming material, or may have a speed difference in the forward or reverse direction. By providing a speed difference, it is possible to control which side the electrode forming material sticks to. When sandwiched between objects with different speeds, in many cases, the electrode forming material is more likely to stick to the object with the faster speed. It is preferable to perform the squeezing process in two or more stages to gradually reduce the thickness rather than in one stage, since this reduces the stress on the electrode forming material. In addition, when controlling the thickness accuracy of the electrode molding material to a high accuracy of, for example, within ±5%, it is preferable to roughly adjust the thickness and then fine-adjust it with a curved surface having a curvature radius of 0.5 mm or more. The thickness accuracy of the electrode can be improved by smoothing the electrode molding material with a curved surface having a curvature radius of 0.5 mm or more. In this case, it may be the curved surface or the electrode molding material that is moving, or both of them may be moved. It is preferable to smooth with a constant pressure, and the pressure is preferably strong enough not to change the average thickness of the electrode by 1% or more.
[0088] In addition, when a roll is used to crush the electrode forming material, the surface of the roll is preferably non-adhesive, and more preferably made of ceramic, fluorine-based polymer or silicone-based polymer, or metal. The roll surface may be treated to increase the surface roughness, such as by making it matte. The surface roughening treatment can be performed by sandblasting or the like. If the surface is roughened too much, the electrode forming material may be buried in the holes (concave portions), so it is preferable that the difference in roughness is small, and the arithmetic mean roughness (Ra) of the surface is preferably 10 μm or less, more preferably 5 μm or less, and more preferably 2 μm or less. In addition, it is preferable that the major axis of the hole is short. The average length of the surface elements (Rsm) is preferably 500 μm or less, more preferably 300 μm or less, and more preferably 200 μm or less. In addition, a tape of a constant thickness may be attached to the surface of the roll to control the thickness of the electrode to be manufactured. Furthermore, a pattern may be applied to the surface of the roll and the pattern may be transferred to the electrode forming material. In addition, from the viewpoint of suppressing the volatilization of components from the electrode forming material, it is preferable that the roll has a small diameter. Furthermore, from the viewpoint of preventing the electrode forming material from sticking to the roll, it is preferable that the surface of the electrode forming material that contacts the roll is corrugated or unevenly formed, for example, by using a method such as shaping or notching. The height difference of the corrugation or unevenness is preferably 1 to 95% of the thickness of the thickest part of the electrode forming material. Shaping can be performed by making the shape of the outlet die of the kneader corrugated, etc. In addition, by imparting the above-mentioned shape to the surface of the electrode forming material, the electrode forming material becomes easily crushed, making it easier to control the thickness.
[0089] In the electrode manufacturing method of the present invention, it is preferable to measure the thickness of the electrode molding material and feedback-control the basis weight of the electrode molding material. The electrode molding material has a ratio of compounds with a volatility rate equal to or higher than that of N-methylpyrrolidone of 0% by mass to 20% by mass, and the basis weight can be easily determined from the thickness. If the thickness is measured and the basis weight is feedback-controlled, the basis weight can be easily controlled. The thickness can be easily measured using a contact thickness gauge or a laser thickness gauge.
[0090] It is preferable that the electrode produced according to the production method of the present invention is incorporated into the electrochemical device as soon as possible after production, and the electrode is preferably incorporated within 20 days, more preferably within 10 days, and even more preferably within 5 days.
[0091] (Electrode recycling method) The method for recycling the electrode of the present invention is a method for recycling the electrode of the present invention formed by attaching an electrode molding material to a current collector, and includes a step of peeling off the electrode molding material from the current collector. In this way, by peeling off the electrode molding material from an electrode formed by providing a portion made of the electrode molding material on the current collector, the peeled electrode molding material and the current collector can be easily reused. In the electrode of the present invention, since the electrode molding material does not have a chemical bond with the current collector, it can be easily peeled off from the current collector. For example, by inserting a spatula with a sharp end as a peeling tool into the interface with the current collector and moving it as it is, the electrode molding material can be peeled off from the current collector without leaving any active material residue. The material of the peeling tool is preferably a material with a lower hardness than the current collector or device with which the peeling tool comes into contact. In addition, it is preferable that the material does not generate conductive fine powder. Examples of materials that satisfy both conditions include, but are not limited to, plastic, rubber, wood, paper, etc. In order to regulate the places where peeling is desired and the places where peeling is not desired, it is also a suitable embodiment to make a preliminary cut in the electrode before peeling. The material of the cutting tool is preferably a material with a hardness lower than that of the current collector or the device with which the cutting tool comes into contact, but the clearance may be controlled so that the cutting tool does not directly come into contact with the current collector or the device. The electrodes to be recycled are not limited to those in the middle of device manufacturing, but may be electrodes generated by discarding or dismantling a device. For the electrodes of the present invention that have not been crosslinked, the active material can be easily separated by further putting them into an organic solvent in which the viscous electrolyte composition can be dissolved, and dissolving the electrolyte composition. The separated active material can be used again in the manufacture of devices. The components constituting the separated viscous electrolyte composition can be reused by refining them by distillation, recrystallization, or the like. The current collector can also be recycled after washing with an organic solvent in which the viscous electrolyte composition residue can be dissolved.
[0092] (Electrochemical Devices) The electrochemical device of the present invention includes the electrode of the present invention and can exhibit good electrochemical properties. Specifically, the electrochemical device of the present invention usually includes a positive electrode, a negative electrode, and an electrolyte, and optionally further includes a separator. The electrochemical device of the present invention requires that at least one of the positive electrode and the negative electrode is the electrode of the present invention.
[0093] In particular, in the electrochemical device of the present invention, one of the positive electrode and the negative electrode is the electrode of the present invention, and the counter electrode of the electrode of the present invention is preferably made of at least one selected from alkali metals, alkaline earth metals, and metallic aluminum. The electrode of the present invention, which can be manufactured in an open atmosphere, may contain more moisture than conventional electrodes, but by using the above-mentioned counter electrode, the moisture brought in from the electrode can be effectively captured.
[0094] In the electrochemical device of the present invention, at least one of the counter electrode and the separator preferably contains an inorganic filler having moisture trapping ability and / or an ionic substance having moisture trapping ability. If the counter electrode or the separator contains an inorganic filler having moisture trapping ability and / or an ionic substance having moisture trapping ability, moisture brought in from the electrode can be effectively trapped.
[0095] Here, the separator is not particularly limited, and any separator that can be used in the field of electrochemical devices can be used. The electrolyte is not particularly limited, and it is preferable to use the same composition as the viscous electrolyte composition contained in the electrode forming material. The inorganic filler having moisture trapping ability is not particularly limited, and for example, silica, alumina, magnesium sulfate, calcium sulfate, magnesium oxide, calcium oxide, magnesium hydride, lithium hydride, calcium hydride, or phosphorus pentoxide particles can be used. The ionic substance having moisture trapping ability is not particularly limited, and for example, bis(oxalate)borate salt, difluorooxalate borate salt, etc. can be used. EXAMPLES
[0096] First, the following Reference Example 1 was carried out to evaluate the volatility of each compound.
[0097] (Reference example 1) In a dry room controlled at a room temperature of 18°C and a dew point of -40°C or less, 1g of each of the organic compounds shown in Table 1 was weighed out onto an aluminum dish with a diameter of 5cm and placed, without a lid, in a draft chamber controlled at a wind speed of 0.5m / min. After 12 hours, the weight was measured and the volatilization rate (= (reduced mass / initial mass) x 100%) was evaluated. The results are shown in Table 1.
[0098] [Table 1]
[0099] Example 1 5 g of ethylene carbonate and 2 g of dimethyl sulfone as low volatile compounds, 1 g of 1,3,2-dioxathiolane-2,2-dioxide as a negative electrode protectant, 1 g of ethylene oxide-allyl glycidyl ether random copolymer with a molecular weight of 1 million as a polymer (ethylene oxide:allyl glycidyl ether (molar ratio) = 90:10), and 1 g of LiBF4 as an ionic substance were weighed out and mixed at room temperature to obtain a uniform viscous electrolyte composition. This operation was performed in the open, but may also be performed in a closed container. The ionic conductivity of the obtained viscous electrolyte composition was 5.6 x 10 -3 It was S / cm. 10 g of the viscous electrolyte composition and 40 g of graphite (604A, manufactured by Nippon Carbon Co., Ltd.) serving as a negative electrode active material were kneaded in an open mortar to obtain a uniform clay-like electrode forming material. This electrode molding material could be made into a thin layer even without a support. When the thickness was reduced to 200 μm, it could be picked up with tweezers as a small piece of about 6 mm square while maintaining its shape. Since this electrode forming material has a tendency to clump together, the entire amount could be neatly transferred from the mortar, with almost no material remaining in the mortar. All of the obtained electrode forming materials were rolled out into a sheet having a thickness of 50 μm on a horizontal table using a metal hand roller having a diameter of 30 mm, and then attached to a copper foil having a thickness of 25 μm as a current collector to produce a negative electrode for a lithium ion battery. The electrode molding material attached to the current collector initially had uneven thickness, but by repeatedly rolling it with a hand roller, the thickness unevenness was reduced to within ±2%. The working time was about 1 hour, and the weight of the obtained negative electrode was 50.0g, not including the current collector, and it was considered that there was almost no loss of material in the manufacturing process. In addition, when the specific gravity of the produced negative electrode was measured, it almost matched the value (theoretical value) calculated from the specific gravity of each material used in the manufacturing, and it was considered that the part made of the electrode molding material had almost no pores. The density of the obtained negative electrode is shown in Table 2 together with the volume percentage of the active material.
[0100] Example 2 6 g of ethylene carbonate and 2 g of dimethyl sulfone as low-volatile compounds, 1 g of a random copolymer of ethylene oxide and propylene oxide with a molecular weight of 1 million (ethylene oxide: propylene oxide (molar ratio) = 90:10) as a polymer, and 41 g of LiBF4 as an ionic substance were weighed out and mixed at room temperature to obtain a uniform viscous electrolyte composition. The ionic conductivity of the obtained viscous electrolyte composition was 5.0 × 10 -3 It was S / cm. 10 g of the viscous electrolyte composition, 25 g of lithium cobalt oxide (Cellseed C, manufactured by Nippon Chemical Industry Co., Ltd.) as a positive electrode active material, and 5 g of acetylene black as a conductive filler were kneaded in an open mortar to obtain a uniform clay-like electrode molding material. This electrode molding material could be made into a thin layer even without a support. When the thickness was reduced to 200 μm, it could be picked up with tweezers as a small piece of about 6 mm square while maintaining its shape. Since this electrode forming material has a tendency to clump together, the entire amount could be neatly transferred from the mortar, with almost no material remaining in the mortar. All of the obtained electrode forming materials were rolled out into a sheet having a thickness of 50 μm on a horizontal table using a metal hand roller having a diameter of 30 mm, and then attached to an aluminum foil having a thickness of 25 μm as a current collector to produce a positive electrode for a lithium ion battery. The electrode molding material attached to the current collector initially had uneven thickness, but by repeatedly rolling it with a hand roller, the thickness unevenness was reduced to within ±2%. The working time was about 1 hour, and the weight of the obtained positive electrode was 40.0g, not including the current collector, and it was considered that there was almost no loss of material in the manufacturing process. In addition, when the specific gravity of the produced positive electrode was measured, it almost matched the value (theoretical value) calculated from the specific gravity of each material used in the manufacturing, and it was considered that the part made of the electrode molding material had almost no pores. The density of the obtained positive electrode is shown in Table 2 together with the volume ratio of the active material.
[0101] [Table 2]
[0102] Example 3 The negative electrode prepared in Example 1, the separator (Polypore, Celgard 2325) impregnated with the viscous electrolyte composition prepared in Example 1, and the positive electrode prepared in Example 2 were stacked in this order, inserted into an aluminum laminate exterior, degassed in a vacuum for 1 minute, and then the ends were heat-sealed to produce a lithium-ion battery. No weight loss was observed before and after vacuum sealing. Immediately after production, this battery was charged and discharged at 25°C and a 0.1C rate, and it was confirmed that it worked well. The initial irreversible capacity was 15%, which is the same as that of existing lithium-ion batteries, and the discharge capacity after 10 cycles was as high as 99% of the initial capacity.
[0103] Comparative Example 1 A planetary mixer was charged with 100 parts of lithium cobalt oxide (Cellseed C, manufactured by Nippon Chemical Industry Co., Ltd.) as an active material and 3 parts of acetylene black as a conductive filler, and N-methylpyrrolidone was added so that the solid concentration was 90%, and the mixture was stirred and mixed for 20 minutes. Then, 1 part of polyvinylidene fluoride was added based on the solid content, and the mixture was kneaded for 90 minutes at a solid concentration of 82%, and then N-methylpyrrolidone was added to adjust the slurry viscosity. This slurry was used to manufacture a positive electrode according to a general manufacturing method for electrodes for lithium-ion batteries. The slurry remained on the walls of the mixer and in the piping, and it took a lot of effort to clean it. The slurry remaining in the container was discarded because it could not be used any more. Then, the electrodes were compressed to a predetermined density and subjected to high-pressure roll pressing in order to reduce thickness unevenness. The finished electrode had a larger weight per unit area at the edges than at the center, which is due to the fact that the edges always rise up when the slurry is applied. In addition, drying the electrodes in an oven required a lot of effort and energy. A battery was made using this electrode and electrolyte was poured into it. The electrolyte was directly poured into the battery container, with the opening of the container kept as small as possible, and the inside and surrounding areas of the container were filled with an argon atmosphere. When charging and discharging was started immediately after the electrolyte was poured into the battery, the initial irreversible capacity was large at 25%, and the discharge capacity rapidly decreased to 80% of the initial capacity after 10 cycles. It is believed that because charging and discharging was started immediately after the battery was manufactured, the electrolyte did not sufficiently penetrate into the battery.
[0104] Comparative Example 2 As a manufacturing method not including the polymer (P), an electrode and a battery were manufactured by the method disclosed in Example 1 of JP-A-2017-534164. However, unlike the method of the present invention, the semi-solid material remained on the walls of the mixer, the piping, and everywhere in the equipment, and cleaning required a lot of effort. There was no need for a high-pressure press to crush the electrodes to the specified density, but when the mixture ratio of the active material was increased in an attempt to obtain a high density, the material did not stick together, making it impossible to obtain a high active material density. In addition, although there was no need to dry the electrodes, the rapid evaporation of GBL, a component of the electrolyte, made the process difficult and workers sometimes choked on the vapors. When measuring the thickness of the electrode, the electrode was too soft and the probe (5mmφ) of the film thickness gauge was pressed against it, causing a dent, making it impossible to measure the film thickness accurately. This is a major problem in terms of product production management. In addition, we tried to remove the excess part of the electrode, but although we were able to do so, there was still residue left behind, and it was not possible to remove it completely. Such residue could lead to a short circuit in the battery. They created a battery using this electrode, immediately began charging and discharging it, and confirmed that it worked.
[0105] Comparative Example 3 A positive electrode for a lithium-ion battery was manufactured using the method disclosed in Japanese Patent No. 4593114, which does not contain low molecular weight organic compounds. Unlike the method of the present invention, the material was too hard to process at room temperature, and it was necessary to heat it to about 120°C. In addition, a decrease in the molecular weight of the polymer was observed due to shearing at high temperatures. There was no need for a high-pressure press to crush the electrodes to the specified density, but increasing the mixture ratio of the active material in an attempt to obtain a high density made kneading impossible, and it was not possible to obtain a high active material density. In addition, when the thickness of the electrode was measured after it had cooled to room temperature, it was found to have a thickness unevenness of about ±10%. However, the electrode could not be deformed even if it was pressed after it had cooled to room temperature, and the thickness unevenness could not be improved. A battery was made using this electrode, and it was placed in a thermostatic chamber at 60°C. After five hours, charging and discharging were started and it was confirmed that the battery worked.
[0106] Example 4 A total of seven screw-type quantitative feeders were used to feed the mixture into a twin-screw extruder (L / D=30) with a kneading section and a vent section, and a T-die that can be discharged in sheet form, with a mass ratio of 5 ethylene carbonate, 2 dimethyl sulfone, 1 ethylene oxide-propylene oxide copolymer with a molecular weight of 1 million, 1 PTFE as a fiber component, 1 lithium bis(fluorosulfonyl)imide, 100 lithium cobalt oxide, and 3 acetylene black, and the mixture was kneaded and formed into a sheet at room temperature of 25°C. The clearance at the die outlet was 100μm, and the mixture was sandwiched from both sides with a PET film with release properties moving at a speed of 12m / min, and nipped with an air pressure of 0.7MPa with a chrome-plated iron roll with a diameter of 200mm to continuously obtain a sheet-shaped positive electrode film with a thickness of 100μm and a thickness accuracy of ±3%. The product temperature during this manufacturing process was 25°C at the inlet of the extruder, the same as room temperature, 50°C in the sealed kneading section due to frictional heat caused by kneading, and 25°C at the outlet, the same as room temperature. Since volatile substances from the material were not completely zero, local exhaust equipment was appropriately installed and operated from the perspective of worker health. The obtained positive electrode film was further smoothed with a mirror-finished SUS plate with a curvature of 300 mm in diameter to improve the film thickness accuracy to ±1%. The obtained electrode was a good electrode with no difference in thickness or density between the center and the edge. In addition, this electrode could be picked up with tweezers even if it was at least 5 cm square. It is thought to have high strength because it contains fibrous components.
[0107] Example 5 A positive electrode film was obtained in the same manner as in Example 4, except that silicone oil at a temperature of 20°C was flowed as a coolant in the barrel of the twin-screw extruder. The product temperature during this production process was 25°C, the same as room temperature, at the inlet of the extruder, and although the temperature rose in the sealed kneading section due to frictional heat caused by kneading, it was kept at 30°C, and at the outlet it was 25°C, the same as room temperature. After confirming that the temperature rise was minimal, devolatilization was performed using a vacuum pump through the vent, and production was successful without any problems.
[0108] Example 6 The die of the twin-screw extruder in Example 4 was changed to one capable of discharging in a cylindrical shape with a diameter of 1 mm, and 10 of these were arranged side by side at intervals of 8 mm. The mass ratios of ethylene carbonate, dimethyl sulfone, ethylene oxide-propylene oxide copolymer with a molecular weight of 1 million, PTFE as a fiber component, lithium bis(fluorosulfonyl)imide, lithium cobalt oxide, and acetylene black were respectively 5, 100, and 3, and the mixture was fed using a screw-type quantitative feeder, and twin-screw kneaded at room temperature of 25°C and discharged in a cylindrical shape with a diameter of 1 mm, and continuously fed onto an aluminum foil with a thickness of 25 μm moving at 30 m / min. The electrode forming material was thinned by sandwiching it between 100 mm diameter nip rolls made of SUS treated with chromium oxide, and then nipped with a silicone-treated 30 mm roll to improve the thickness accuracy, and a sheet-shaped positive electrode was obtained in which the thickness of the part made of the electrode forming material was 98 μm and the film thickness accuracy was ±1%. The product temperature during this manufacturing process was 25°C at the inlet of the extruder, the same as room temperature, in the sealed kneading section the temperature rose to 50°C due to frictional heat caused by kneading, and at the outlet it was 25°C, the same as room temperature.
[0109] Example 7 Two twin-screw extruders of Example 6 were arranged in parallel to attempt the manufacture of a negative electrode simultaneously on both sides of a current collector foil. The electrode molding material was weighed and charged so that the mass ratio was 5 ethylene carbonate, 2 dimethyl sulfone, 1 ethylene oxide-propylene oxide copolymer with a molecular weight of 1 million, 0.5 PTFE as a fiber component, 1 lithium bis(fluorosulfonyl)imide, and 50 graphite as a negative electrode active material, and supplied onto a 300 mm diameter matte-treated SUS roll (Ra = 0.82 μm, Rsm = 112 μm) rotating at a peripheral speed of 50 m / min, and a small diameter roll with a diameter of 30 mm was applied to this roll with a clearance of 100 μm, and rotated in the opposite direction to the 300 mm diameter roll to make the electrode molding material thin. This device was placed symmetrically on both sides of a 25 μm thick copper foil moving at 50 m / min, and the copper foil was nipped between the 300 mm rolls. The electrode forming material was transferred to both sides of the current collector foil simultaneously without falling off the large diameter roll, and a negative electrode having a portion made of the electrode forming material on both sides of the copper foil was manufactured. A battery using this negative electrode worked well. In addition, by installing a mechanism to sharply remove the electrode forming material at the end by placing a plastic spatula near the end of the electrode forming material after passing the small diameter roll, the linearity of the end of the portion made of the electrode forming material was improved, the width accuracy of the negative electrode was improved, and the position accuracy of the portions made of the electrode forming material on the front and back was improved. Such an electrode manufacturing is impossible with the existing coating method.
[0110] Example 8 A negative electrode was manufactured in the same manner as in Example 7, except that a current collector foil with through holes (hole diameter 500 μm, aperture ratio 30%) was used. When the manufactured negative electrode was cut, it was confirmed that the through holes were neatly filled with the electrode molding material and that the electrode molding materials on both sides were united. As a result, the energy density was increased by the amount of the holes, and a negative electrode was manufactured in which the electrode molding material was less likely to fall off the current collector due to the unity of the electrode molding materials on both sides.
[0111] Example 9 The electrode forming material used in Example 7 was kneaded with an open roll having two chrome-plated iron rolls with a diameter of 30 mm. The roll gap was gradually narrowed to 1 mm, and the material was kneaded while being turned over until the entire material was uniformly mixed. The product temperature rose to a maximum of 40°C. Finally, the roll gap was adjusted to 100 μm, and the electrode forming material was peeled off from the roll to obtain a negative electrode sheet with a thickness of 100 μm. This negative electrode sheet was attached to a copper foil with a thickness of 25 μm to form a negative electrode. The battery using this negative electrode operated well.
[0112] Example 10 The surface of the sheet-shaped positive electrode having a thickness of 50 μm obtained in Example 2 was scraped off with a milling machine to obtain a positive electrode having a thickness of 40 μm.
[0113] Example 11 When the negative electrode produced in Example 1 was wrapped around a cylinder with a diameter of 1 mm halfway together with the current collector and then returned to its original state, no particular change was observed. This was repeated 100 times, but again no particular change was observed.
[0114] Comparative Example 4 When the negative electrode produced in Comparative Example 1 was wrapped halfway around a cylinder with a diameter of 1 mm together with the current collector and then returned to its original state, a crack appeared in the part made of the electrode molding material. When this was repeated once more, part of the part made of the electrode molding material fell off from the current collector, so the test was terminated.
[0115] Example 12 When a part of the electrode molding material of the negative electrode produced in Example 1 was peeled off with a plastic spatula, the electrode molding material could be peeled off cleanly from the copper foil. Alternatively, the electrode molding material that was peeled off was re-kneaded, placed on the place where it was peeled off, and stretched from above with a roller, allowing the negative electrode to be molded in the same way again. In addition, the regenerated negative electrode was so well-integrated that it was impossible to visually determine where the peeled off part was.
[0116] (Example 13) The entire part of the electrode molding material of the positive electrode produced in Example 7 was peeled off with a plastic spatula, and the peeled piece was put into a twin-screw kneader to produce a positive electrode. The positive electrode could be molded in the same way again. Furthermore, the battery using the recycled positive electrode had the same performance as the original.
[0117] (Reference example 2) A viscous electrolyte composition consisting of 1 g of lithium bis(fluorosulfonyl)imide, 8 g of ethylene carbonate, and 1 g of ethylene oxide-propylene oxide copolymer was thinly spread on a hot plate to a thickness of 1 mm, and a glass plate was placed 1 cm above it to evaluate the degree of volatilization of the components contained in the viscous electrolyte composition. The hot plate temperature was increased from 20°C to 130°C in 10°C increments. The glass began to fog up slightly from 105°C, and became noticeably foggy from 125°C. This is thought to be due to ethylene carbonate volatilizing and condensing from the viscous electrolyte composition. The deposit was solid, and did not adhere to any part other than the top of the viscous electrolyte composition, and the adhered matter did not move.
[0118] (Reference example 3) A viscous electrolyte composition was prepared in the same manner as in Reference Example 2, except that ethylene carbonate was replaced with propylene carbonate, and the degree of volatilization of the components contained in the viscous electrolyte composition was evaluated. The glass became slightly cloudy from 105°C, and the clouding of the glass became noticeable from 125°C. This is thought to be due to propylene carbonate volatilizing from the viscous electrolyte composition and condensing. The deposit was liquid and moved slightly along the glass to the surroundings. Since it was liquid, it was slightly more difficult to visually confirm than the case of solid ethylene carbonate in Reference Example 2. When the experiment was continued until most of the propylene carbonate had volatilized, the phenomenon of some of the propylene carbonate dripping in droplets was also confirmed. If the amount was small, it would not be a problem, but if a large amount of liquid condensate is produced during production, it may have a negative effect on the equipment.
[0119] Example 14 A negative electrode was prepared in the same manner as in Example 1, except that dimethylsulfone was replaced with succinonitrile. The working time was about 1 hour, and the weight of the obtained negative electrode was 40.0 g excluding the current collector, and it was considered that there was almost no loss of material in the manufacturing process.
[0120] Example 15 A negative electrode was produced in the same manner as in Example 1, except that dimethylsulfone was replaced with propylene carbonate. The working time was about 1 hour, and the weight of the obtained negative electrode was 39.9 g not including the current collector, and it was considered that a small amount of propylene carbonate was lost during the manufacturing process.
[0121] (Example 16) The same operation as in Example 15 was carried out, except that the area where the kneading work was carried out was simply covered with an acrylic plate to prevent it from being exposed to the air currents in the dry room. The weight of the obtained negative electrode was 40.0 g excluding the current collector, and it was considered that there was almost no loss of material in the manufacturing process.
[0122] (Example 17) A negative electrode was prepared in the same manner as in Example 16, except that propylene carbonate was replaced with triethyl phosphate. The working time was approximately 1 hour, and the weight of the obtained negative electrode was 39.9 g excluding the current collector. Although some material was lost in the manufacturing process, the amount was considered to be small.
[0123] Comparative Example 5 2 g of ethylene carbonate as a low volatility compound, 5 g of γ-butyrolactone as a high volatility compound, 1 g of 1,3,2-dioxathiolane-2,2-dioxide as a negative electrode protective agent, 1 g of an ethylene oxide-propylene oxide copolymer having a molecular weight of 1,000,000 as a polymer, and 1 g of LiBF4 as an ionic substance were weighed out and mixed at room temperature to prepare a uniform viscous electrolyte composition. Then, a lithium ion battery negative electrode was produced in the same manner as in Example 1. The smell of gamma-butyrolactone was in the air during work. The working time was about 1 hour, and the weight of the obtained negative electrode was 38.9 g not including the current collector. It was determined that most of the weight loss was due to volatilization of γ-butyrolactone during the manufacturing process.
[0124] (Example 18) 6 g of ethylene carbonate as a low volatility compound, 1 g of γ-butyrolactone as a high volatility compound, 1 g of 1,3,2-dioxathiolane-2,2-dioxide as a negative electrode protective agent, 1 g of an ethylene oxide-propylene oxide copolymer having a molecular weight of 1 million as a polymer, and 1 g of LiBF4 as an ionic substance were weighed out and mixed in a dry room controlled at a room temperature of 5°C to prepare a uniform viscous electrolyte composition. Then, the same procedure as in Example 1 was carried out, but more quickly, to produce a lithium ion battery negative electrode. During work, there was a faint odor of γ-butyrolactone. The working time was about 30 minutes, and the weight of the obtained negative electrode was 39.9 g not including the current collector.
[0125] Comparative Example 6 A negative electrode for a lithium ion battery was produced in the same manner as in Example 1, except that dimethylsulfone was replaced with dimethyl carbonate. During work, there was a strong smell of dimethyl carbonate in the air. The working time was about 1 hour, and the weight of the obtained negative electrode was 38.0 g not including the current collector. It was determined that the entire amount of the added dimethyl carbonate had volatilized during the manufacturing process.
[0126] (Example 19) A lithium ion battery was produced in the same manner as in Example 3, except that the work was carried out in an environment with a humidity of 5% (dew point: -13°C) that was not a dry room. We immediately charged and discharged the battery and confirmed that it worked, but the discharge capacity retention rate after 10 cycles at 0.1C in the voltage range of 4.2-3.0V was only 50%.
[0127] (Example 20) A positive electrode was produced in the same manner as in Example 2, except that the work was carried out in an environment with a humidity of 5% (dew point: -13°C) rather than in a dry room. This positive electrode was transferred to a dry room with a dew point of -40°C, and immediately, a 200μm-thick lithium foil as a negative electrode having moisture trapping ability, a separator, and the positive electrode of this example were stacked in that order, inserted into an aluminum laminate exterior, degassed in a vacuum for 1 minute, and then the ends were sealed with heat to produce a lithium-ion battery. When it was immediately charged and discharged, it was confirmed that it worked, and after 10 cycles at 0.1C in the voltage range of 4.2-3.0V, the discharge capacity retention rate was improved to 90%.
[0128] Example 21 For the purpose of drying the positive electrode produced in Example 20, the positive electrode was moved to a dry room, and left overnight in a place where it was gently exposed to a dry air current. The weight of the positive electrode after leaving it was 39.8 g, and the weight loss was slight. Next, a 200 μm thick lithium foil as a negative electrode having moisture trapping ability, a separator, and the positive electrode of this example were laminated in that order, inserted into an aluminum laminate exterior, degassed in a vacuum for 1 minute, and then the ends were sealed with heat to produce a lithium ion battery. When immediately charged and discharged, it was confirmed that the battery worked, and the discharge capacity retention rate after 10 cycles at 0.1 C in the voltage range of 4.2-3.0 V was improved to 95%.
[0129] Example 22 A lithium ion battery was manufactured in the same manner as in Example 3, except that 2% of lithium bis(oxalate)borate, which has moisture trapping properties, was added as an ionic substance. When the battery was immediately charged and discharged, it was confirmed that it worked, and the discharge capacity retention rate after 10 cycles at 0.1 C in the voltage range of 4.2-3.0 V was improved to 99.5%. This is thought to be due to the fact that the oxalate borate structure of the bis(oxalate)borate ion has the ability to react with moisture and trap water, and a similar effect can be expected for related difluorooxalate borate salts.
[0130] Example 23 The positive electrode sandwiched between the PET films having releasability produced in Example 4 was punched out into a doughnut shape (outer diameter 5 cm, inner diameter 4 cm) with a punching die, and aluminum foil as a current collector was punched out to a size 1 mm larger than the doughnut on the inside and outside and laminated to produce a positive electrode. A separator was punched out to a size 2 mm larger than the positive electrode current collector on the inside and outside and laminated, and a doughnut-shaped Li metal was arranged as a negative electrode to form a battery. Furthermore, an exterior was applied with aluminum laminate punched out into a doughnut shape, and a doughnut-shaped lithium ion battery with an outer diameter of 7 cm and an inner diameter of 2 cm was obtained. In the same manner, lithium ion batteries such as a figure-8 shape, a star shape, and an S shape could also be manufactured. The scraps generated by punching can be used as material for new electrodes by returning them to the kneading process as they are. Manufacturing a device of such a shape is extremely difficult with conventional technology, and even if it is made, it is extremely unprofitable due to the large amount of waste of material.
[0131] (Example 24) A 10 cm wide aluminum foil with a 6 cm wide conductive carbon coating of 1 μm thickness was used as a current collector to manufacture a positive electrode in the same manner as in Example 6. The electrode molding material was peeled off from the edge with a plastic spatula and pulled up with tweezers. It peeled off smoothly up to the boundary with the conductive carbon coat, and the electrode molding material was neatly broken along the boundary line. After that, the electrode molding material on the carbon coat was peeled off again with a plastic spatula, and although a slightly stronger force was required, it was able to be peeled off neatly. It was found that the adhesion between the electrode molding material and the current collector was improved by applying a carbon coat. It was also found that such a treatment made it possible to regulate the areas where the electrode molding material was to be placed and the areas where it was not to be placed.
[0132] (Example 25) Except for changing 25 g of lithium cobalt oxide to 10 g of silicon with an average particle size of 10 μm, a negative electrode was produced in the same manner as in Example 2. The obtained negative electrode could be thinned without a support, as in Example 2, and when the thickness was made 200 μm, it could be picked up with tweezers as a small piece of at least about 6 mm square while maintaining its shape.
[0133] (Example 26) A negative electrode was produced in the same manner as in Example 25, except that 10 g of silicon having an average particle size of 10 μm was replaced with 10 g of silicon having an average particle size of 100 nm. The obtained negative electrode could be thinned without a support, as in Example 25, and when the thickness was made 200 μm, it could be picked up with tweezers as a small piece of at least about 20 mm square while maintaining its shape, and it was found that the strength was improved compared to Example 25. This is thought to be due to the fact that the surface area was increased by the small particle size, and the adhesive interface with the viscous electrolyte composition was increased.
[0134] Example 27 5 g of succinonitrile, 2 g of dimethyl sulfone, 1 g of succinic anhydride, 1 g of ethylene oxide-epichlorohydrin-allyl glycidyl ether random copolymer with a molecular weight of 500,000, and 41 g of LiBF were weighed out and mixed at room temperature to prepare a uniform viscous electrolyte composition. The ionic conductivity of this viscous electrolyte composition was 2.2 × 10 -3 This viscous electrolyte composition could be used to form an electrode molding material in the same manner as in Examples 1 and 2, and could be processed into an electrode.
[0135] (Example 28) 6 g of ethylene carbonate, 2 g of dimethyl sulfone, 1 g of Blenmer (registered trademark) PME-400 (methoxypolyethylene glycol-methacrylate having 9 ethylene oxide chains in the side chain) homopolymer with a molecular weight of 100,000, and 41 g of LiBF were weighed out and mixed at room temperature to prepare a uniform viscous electrolyte composition. The ionic conductivity of this viscous electrolyte composition was 5.2 × 10 -3 This viscous electrolyte composition could be used to form an electrode molding material in the same manner as in Examples 1 and 2, and could be processed into an electrode.
[0136] (Example 29) 1 g of acrylic rubber having a molecular weight of 400,000, which is a 1:1 copolymer of ethyl acrylate and butyl acrylate, 4 g of ethylene carbonate, 4 g of succinonitrile, and 1 g of LiPF6 were weighed out and mixed at room temperature to prepare a uniform viscous electrolyte composition. The ionic conductivity of this viscous electrolyte composition was 6.0 × 10 -3 This viscous electrolyte composition could be used to form an electrode molding material in the same manner as in Examples 1 and 2, and could be processed into an electrode.
[0137] (Example 30) 1 g of acrylic rubber having a molecular weight of 400,000, which is a 1:1 copolymer of ethyl acrylate and butyl acrylate, 4 g of ethylene carbonate, 2 g of succinonitrile, 1 g of dimethyl sulfone, and 3 g of magnesium bis(trifluoromethanesulfonyl)imide were weighed out and mixed at room temperature to prepare a uniform viscous electrolyte composition. The ionic conductivity of this viscous electrolyte composition was 3.6×10-3 This viscous electrolyte composition could be used to form an electrode molding material in the same manner as in Examples 1 and 2, and could be processed into an electrode.
[0138] (Example 31) 2 g of ethylene carbonate, 2 g of dimethyl sulfone, 2 g of diglycolic anhydride, 2 g of sulfolene, 1 g of polyethylene glycol having a molecular weight of 1 million (manufactured by Aldrich), and 1 g of lithium bis(trifluoromethanesulfonyl)imide were weighed out and mixed at room temperature to prepare a uniform viscous electrolyte composition. The ionic conductivity of this viscous electrolyte composition was 2.1 × 10 -3 This viscous electrolyte composition could be used to form an electrode molding material in the same manner as in Examples 1 and 2, and could be processed into an electrode.
[0139] Comparative Example 7 4.5g of ethylene carbonate, 4.5g of propylene carbonate, 1g of polyvinylidene fluoride-hexafluoropropylene copolymer (manufactured by Aldrich), and 3g of lithium bis(trifluoromethanesulfonyl)imide were weighed out, heated to 100°C, and mixed to obtain a homogeneous electrolyte composition. When this electrolyte composition was cooled to room temperature, it gelled and became a composition with no viscosity. This is thought to be because the polyvinylidene fluoride-hexafluoropropylene copolymer precipitated microscopically at room temperature and became incompatible. Graphite was added in the same manner as in Example 1, and this was kneaded in a mortar for processing, but it crumbled and could not be processed.
[0140] Example 32 Positive electrodes were produced in the same manner as in Example 5, except that the clearance of the die outlet was set to 200 μm, 500 μm, 1 mm, and 1 cm. Positive electrodes having thicknesses of 200 μm, 500 μm, 1 mm, and 1 cm were obtained, respectively, and all of them could be produced with a thickness accuracy of within 1%, and the electrode density also agreed well with the calculated value, so they are considered to be dense electrodes without pores.
[0141] (Example 33) A positive electrode was manufactured in the same manner as in Example 6, except that the diameter of the die outlet was 300 μm, the number of outlets was 20, and the interval was 4 mm. A positive electrode with an average thickness of 32 μm was manufactured, and the thickness precision was 3%. The electrode density also agreed well with the calculated value, so it is considered to be a dense electrode without pores.
[0142] (Example 34) A Li metal foil was attached to the negative electrode of Example 1 and vacuum sealed in an aluminum laminate packaging material. This was stored in an oven at 60 ° C for about 2 hours, and then left at room temperature, and the color of the negative electrode changed from black to gold. This indicates that the negative electrode graphite was doped with Li metal, and it was found that the electrode could be easily pre-doped. In addition, the excess Li metal that remained after doping could be easily peeled off from the negative electrode. This pre-doped electrode was combined with an electrode using lithium titanate as an active material, which was produced separately according to the present invention, and a battery was produced according to Example 3, and repeated charging and discharging was possible. The handling of this pre-doped negative electrode, including the production of the battery, was carried out in an argon glove box.
[0143] (Experimental Example 1) 40 g of dimethyl carbonate was added to the electrode forming material of Example 2 to form a slurry. Using this as ink, an inkjet printer was used to form a large number of dots with a diameter of about 100 μm on an aluminum foil of 1 cm x 1 cm with a gap of about 1 mm. After this, the dimethyl carbonate was volatilized to form a dome-shaped positive electrode dot. Furthermore, the surface was stroked with a stainless steel spatula having a curvature radius of 20 cm to flatten the top of the dot to form a positive electrode. A separator cut to 1.2 cm x 1.2 cm was placed on this positive electrode, and a lithium foil of 1 cm x 1 cm was placed on top to form a lithium metal secondary battery. When the battery was immediately charged and discharged, it was confirmed that it worked well.
[0144] (Example 35) The clay-like electrode molding materials for the positive and negative electrodes obtained in Examples 1 and 2 were placed in aluminum laminate zip bags purged with argon, heat sealed, and stored at 25°C. When removed from the bags one year later, no changes in appearance were observed in either case, so lithium ion batteries were manufactured according to Examples 1 to 3 and charged and discharged, with the same results as in Example 3. It was found that the electrode molding material of the present invention has excellent storage stability.
[0145] (Example 36) A lithium ion battery was manufactured by sandwiching Celgard 2325 (made by Polypore) between the negative electrode of Example 1 and the positive electrode of Example 2, and wrapping them in aluminum laminate. At this point, the Celgard was not wet. The battery of Example 3 was in a working state at the time of manufacture, so the electrical insulation resistance of the separator could not be measured, but the insulation resistance could be measured by the method of this example. After measuring the insulation resistance, 1M LiPF6 and ethylene carbonate / dimethyl carbonate (50:50) were injected as electrolyte and heat sealed. The battery was charged and discharged the next day, and it was confirmed that it worked. In this case, either the positive or negative electrode may be an electrode made by the coating method.
[0146] (Example 37) A lithium ion battery was manufactured by combining the positive electrode of Example 2, Celgard 2325 (manufactured by Polypore), and a metal Li negative electrode, and wrapping them in an aluminum laminate. The insulation resistance of this battery could also be measured. After measuring the insulation resistance, dimethyl carbonate was injected as a solvent instead of an electrolyte, and the battery was heat-sealed. The battery was charged and discharged the next day, and it was confirmed that it worked. The injected solvent does not contain salt, but it is believed that after injection, lithium salt migrated from the positive electrode, and lithium ions were also supplied to the separator, making it possible to operate. In this case, the negative electrode may be an electrode made by a coating method. Since a solvent that does not contain salt is injected, the viscosity is low, which is advantageous for liquid circulation.
[0147] (Example 38) A lithium ion battery was manufactured by combining a separator made of a random copolymer of ethylene oxide-allyl glycidyl ether with a molecular weight of 1 million (ethylene oxide:allyl glycidyl ether (molar ratio) = 90:10) containing 1% 2,2-dimethoxy-2-phenylacetophenone (manufactured by Wako Pure Chemical Industries) as a transparent film-like UV crosslinking agent and crosslinking by UV irradiation, the positive electrode of Example 2, and a metallic Li negative electrode, and wrapping them in an aluminum laminate. The insulation resistance of this battery was also measured. After measuring the insulation resistance, the battery was stored at 25°C for 5 days, and then charged and discharged, confirming that it worked.
[0148] (Example 39) A 20 mm square negative electrode with a crosslinked polymer was produced in the same manner as in Example 1, except that 50 mg of dicumyl peroxide was added as a thermal crosslinking agent to the viscous electrolyte composition of Example 1 and the electrode was heated at 160°C for 20 minutes. This negative electrode maintained its shape as a film even without a support such as copper foil, could be picked up with tweezers, and had good handling properties. When the electrode was heated, both sides of the electrode were sandwiched between copper foil to suppress the volatilization of low molecular weight organic compounds. However, once the electrode has been crosslinked, it can no longer be recycled by returning it to the upstream of the process.
[0149] (Example 40) After producing an electrode forming material in the same manner as in Examples 1 and 2, the material was crushed as finely as possible and then transferred onto a current collector. This was carefully rolled out using a hand roller while adjusting the pressure applied, and the thickness and thickness precision were controlled to produce positive and negative electrodes with a porosity of 10% by volume, which is higher than that of Examples 1 and 2. As in Examples 1 and 2, no loss of material was observed during the work. Using these materials, a battery was created in the same manner as in Example 3. When the electrode and separator were attached, slight air bubbles were confirmed to have been generated from the electrode. It is believed that the viscous electrolyte composition supplied from the separator expelled the air in the pores of the electrode. The generation of air bubbles ceased within 5 seconds, so the generated air bubbles were pushed out of the electrode to complete the battery. The initial irreversible capacity was 16%, and the discharge capacity after 10 cycles was 99% of the initial capacity.
[0150] (Example 41) Positive and negative electrodes having a porosity of 15% by volume were produced in the same manner as in Example 40. As in Example 40, no loss of material was observed during the operation. Using these, a battery was made in the same manner as in Example 3. When the electrode and the separator were attached, it was confirmed that air bubbles were generated from the electrode in the same manner as in Example 40. The generation of air bubbles stopped within 10 seconds, so the generated air bubbles were pushed out of the electrode to complete the battery. The initial irreversible capacity was 17%, and the discharge capacity after 10 cycles was 99% of the initial capacity.
[0151] (Example 42) Positive and negative electrodes having a porosity of 20% by volume were produced in the same manner as in Example 40. As in Example 40, no loss of material was observed during the operation. Using these, a battery was made in the same manner as in Example 3. When the electrode and the separator were attached, it was confirmed that air bubbles were generated from the electrode in the same manner as in Example 40. The generation of air bubbles stopped within 30 seconds, so the generated air bubbles were pushed out of the electrode to complete the battery. The initial irreversible capacity was 20%, and the discharge capacity after 10 cycles was 95% of the initial capacity. This decline in performance is believed to be due to an increase in pores in the electrodes, which inhibits ionic and electronic conduction, thereby increasing the resistance inside the battery.
[0152] (Example 43) Carbon nanotubes (CNTs) as a fiber component with a nano-sized fiber diameter having electrical conductivity (ZEON NANO SG101, manufactured by Zeon Nano Technology Co., Ltd., average diameter: 4 nm, average length: 400 μm, BET specific surface area: 1150 m 2 A uniform clay-like electrode molding material was obtained by kneading 5 mg of ethylene oxide-propylene oxide copolymer (molecular weight 100000 / g), 50 mg of ethylene carbonate, 100 mg of dimethyl sulfone, 10 mg of ethylene oxide-propylene oxide copolymer (molecular weight 100000), 10 mg of lithium bis(fluorosulfonyl)imide, and 1 g of lithium cobalt oxide in an open mortar. This electrode molding material can be made into a thin layer even without a support, and when made into a sheet with a thickness of 200 μm, it can be picked up with tweezers as a small piece of at least about 3 cm square while maintaining its shape. It is thought to have high strength because it contains fibrous components. In addition, although the fibers are longer than the thickness of the sheet, no fibers were observed protruding from the sheet.
[0153] (Example 44) 4 g of ethylene carbonate, 4 g of propylene carbonate, 1 g of a random copolymer of ethylene oxide and propylene oxide having a molecular weight of 1 million (ethylene oxide: propylene oxide (molar ratio) = 90: 10) as a polymer, and 1 g of lithium hexafluorophosphate as an ionic substance were weighed out and mixed at room temperature to prepare a uniform viscous electrolyte composition. 1 g of the viscous electrolyte composition, 8 g of lithium cobalt oxide (Cellseed C, average particle size 20 μm, manufactured by Nippon Chemical Industry Co., Ltd.) as a positive electrode active material, 0.5 g of acetylene black as a conductive filler, and 0.08 g of PTFE as a fiber component were kneaded in an open mortar to obtain a uniform clay-like electrode molding material. Further, the viscous electrolyte composition was reduced to 0.8 g, and Li2O-Al2O3-SiO2-P2O5-TiO2 (ion conductive glass, manufactured by OHARA Corporation, average particle size 1 μm, specific gravity 2.8 g / cm) was added as an inorganic solid electrolyte. 30.5 g of ionic substance (S), organic composition (PO), and inorganic solid electrolyte (SE) were added to the mixture to obtain two types of electrode molding materials. The mixing ratio of inorganic solid electrolyte (SE) to the total volume of ionic substance (S), organic composition (PO), and inorganic solid electrolyte (SE) was 23 volume %. All of the electrode molding materials could be made into thin layers without a support. When the thickness was made 200 μm, the electrode molding material to which the solid electrolyte was added could be picked up with tweezers as a small piece of about 6 cm square without losing its shape. Using two types of electrode forming materials, a positive electrode having a thickness of 80 μm was prepared in the same manner as in Examples 2 and 3, and a lithium ion battery was constructed. When this battery was charged and discharged at 25° C. and a rate of 0.2 C immediately after production, a discharge capacity of 143 mAh / g per weight of the positive electrode was obtained in both cases. The performance of the electrochemical device was not impaired even if the organic electrolyte was reduced by using an inorganic solid electrolyte, and the safety of the manufacturing process and the electrochemical device was improved by reducing the amount of flammable organic compounds.
[0154] (Example 45) 4 g of ethylene carbonate, 4 g of propylene carbonate, 1 g of poly(2-ethyl-2-oxazoline) (Sigma-Aldrich) having a molecular weight of 500,000 as a polymer, and 41 g of LiBF4 as an ionic substance were weighed out and mixed at room temperature to prepare a uniform viscous electrolyte composition. 1 g of the viscous electrolyte composition and Li2O-Al2O3-SiO2-P2O5-TiO2 (ion conductive glass manufactured by OHARA Corporation, average particle size 1 μm, specific gravity 2.8 g / cm3) as an inorganic solid electrolyte were 3) and 0.25g of PTFE as a fiber component were kneaded in an open mortar to obtain a composite electrolyte composition containing a viscous electrolyte composition and an inorganic solid electrolyte. The composite electrolyte composition was clay-like, had a tendency to clump together, and could be molded into a sheet. 25g of lithium cobalt oxide (Cellseed C, average particle size 20μm, manufactured by Nippon Chemical Industry Co., Ltd.) as a positive electrode active material and 0.75g of acetylene black as a conductive filler were further added and kneaded to obtain a uniform clay-like electrode molding material. The blending ratio of the inorganic solid electrolyte (SE) to the total volume of the ionic substance (S), organic composition (PO), and inorganic solid electrolyte (SE) was 72% by volume. This electrode molding material could be made into a thin layer without the need for a support. When the thickness was made 200 μm, the electrode molding material to which the solid electrolyte was added could be picked up with tweezers as a small piece of about 7 cm square without losing its shape. A lithium ion battery was constructed by preparing a positive electrode having a thickness of 60 μm in the same manner as in Examples 2 and 3. Immediately after the production, the battery was charged and discharged at 25° C. and a rate of 0.05 C, and a discharge capacity of 143 mAh / g per weight of the positive electrode was obtained. [Industrial Applicability]
[0155] According to the present invention, it is possible to provide an electrode forming material which is easy to prepare, has an active material content that is easily increased, and is unlikely to cause odor or stability problems. Furthermore, according to the present invention, it is possible to provide an electrode and an electrochemical device using the electrode molding material.
Claims
1. An electrode forming material comprising at least one active material (A) and a viscous electrolyte composition, The viscous electrolyte composition comprises at least one ionic substance (S), and an organic composition (P-O) containing at least one polymer (P) and a low molecular weight organic compound (O) having a molecular weight of less than 10,000; the content ratio of the polymer (P) in the organic composition (P-O) is 50 mass% or less, The low molecular weight organic compound (O) contains two or more compounds having a volatility rate lower than that of N-methylpyrrolidone, and the proportion of compounds having a volatility rate equal to or higher than that of N-methylpyrrolidone is 20 mass% or less.
2. The electrode molding material according to claim 1 , further comprising a conductive filler.
3. 3. The electrode forming material according to claim 1, wherein the content of the active material (A) is 50% by volume or more.
4. The electrode forming material according to any one of claims 1 to 3, wherein the content of the active material (A) is 60 volume % or more.
5. The electrode molding material according to any one of claims 1 to 4, wherein the active material (A) is nano-sized.
6. The electrode molding material according to any one of claims 1 to 5, further comprising a fiber component having a nano-sized fiber diameter.
7. The organic composition (P-O) has a content ratio of a compound that is liquid at a temperature of 5 ° C. under atmospheric pressure of 0 mass % or more and 20 mass % or less. The electrode forming material according to any one of claims 1 to 6.
8. The viscous electrolyte composition has an ionic conductivity of 1.0×10 -4 The electrode molding material according to any one of claims 1 to 7, wherein the electrical conductivity is 0.2 S / cm or more.
9. The viscous electrolyte composition has an ionic conductivity of 1.0×10 -4 The electrode molding material according to any one of claims 1 to 8, wherein the electrical conductivity is 100 S / cm or more.
10. A method for producing an electrode having a part formed using the electrode molding material according to any one of claims 1 to 9, A method for manufacturing an electrode, comprising the step of forming the part using the electrode molding material.
11. The method for producing an electrode according to claim 10 , wherein the portion has a porosity of 20% by volume or less.
12. A method for producing the electrode according to claim 10 or 11, comprising a step of forming the electrode forming material according to any one of claims 1 to 9 into a sheet-like film.
13. A method for producing an electrode according to claim 10 or 11, comprising a step of attaching the electrode molding material according to any one of claims 1 to 9 to a current collector.
14. The method for producing an electrode according to claim 13 , wherein the current collector has a through hole at a portion where the electrode molding material is attached.
15. The method for producing an electrode according to claim 13 or 14, wherein the current collector has a conductive coating on a surface that comes into contact with the electrode molding material.
16. The method for producing an electrode according to any one of claims 10 to 15, further comprising a step of crosslinking or polymerizing the electrode molding material.
17. A method for producing an electrode, comprising a step of crushing a plurality of strands made of the electrode forming material according to any one of claims 1 to 9 to form a sheet.
18. A method for producing an electrode, comprising a step of forming the electrode molding material according to any one of claims 1 to 9 into a shape and then attaching the shape to a current collector.
19. A method for producing an electrode, comprising a step of attaching the electrode molding material according to any one of claims 1 to 9 to both sides of a current collector.
20. A method for producing an electrode, comprising a step of crushing the electrode molding material according to any one of claims 1 to 9 with a curved surface having a radius of curvature of 100 mm or less.
21. A method for manufacturing an electrode, comprising a step of scraping off the electrode molding material according to any one of claims 1 to 9 to adjust the thickness and / or shape.
22. A method for manufacturing an electrode, comprising a step of roughly adjusting the thickness of the electrode molding material according to any one of claims 1 to 9 and then fine-adjusting the thickness with a curved surface having a radius of curvature of 0.5 mm or more.
23. The method for manufacturing an electrode according to any one of claims 17 to 22, further comprising a step of measuring a thickness of the electrode molding material and feedback-controlling a basis weight of the electrode molding material.
24. The method for recycling an electrode according to any one of claims 13 to 15, further comprising a step of peeling off the electrode molding material from the current collector.
25. A method for producing an electrochemical device, comprising the step of producing an electrode by using the method for producing an electrode according to any one of claims 10 to 16.
26. 26. The method for producing an electrochemical device according to claim 25, wherein the counter electrode of the electrode is made of at least one selected from an alkali metal, an alkaline earth metal, and metallic aluminum.
27. 27. The method for producing an electrochemical device according to claim 25, wherein at least one of the counter electrode and the separator of the electrode contains an inorganic filler having a moisture trapping ability.
28. 28. The method for producing an electrochemical device according to claim 25, wherein at least one of the counter electrode of the electrode and the separator contains an ionic substance capable of trapping moisture.
29. The method includes a step of crushing a plurality of strands of an electrode forming material into a sheet shape, The electrode forming material comprises at least one active material (A) and a viscous electrolyte composition, The viscous electrolyte composition comprises at least one ionic substance (S), and an organic composition (P-O) containing at least one polymer (P) and a low molecular weight organic compound (O) having a molecular weight of less than 10,000; the content ratio of the polymer (P) in the organic composition (P-O) is 50 mass% or less, The low molecular weight organic compound (O) contains a compound having a volatility rate equal to or higher than that of N-methylpyrrolidone in an amount of 0 mass % or more and 20 mass % or less.
30. A method for manufacturing an electrochemical device including an electrode having a portion formed using an electrode molding material, comprising the steps of: forming the part using the electrode molding material; The electrode forming material comprises at least one active material (A) and a viscous electrolyte composition, The viscous electrolyte composition comprises at least one ionic substance (S), and an organic composition (P-O) containing at least one polymer (P) and a low molecular weight organic compound (O) having a molecular weight of less than 10,000; the content ratio of the polymer (P) in the organic composition (P-O) is 50 mass% or less, The low molecular weight organic compound (O) has a ratio of compounds having a volatility rate equal to or higher than that of N-methylpyrrolidone of 0% by mass or more and 20% by mass or less, At least one of the counter electrode of the electrode and the separator contains an ionic substance capable of trapping moisture.
Citation Information
Patent Citations
Gel polymeric electrolyte and solid electrolyte battery using the same
JP2000058078A
Cathode film for alkali metal polymer battery and manufacturing method thereof
JP2005519442A
battery
JP2006216373A
Manufacturing method of composite material for electrode
JP2006522441A
Method of manufacturing electrode for electrochemical element
JP2010086788A
